Paraneoplastic Nephropathy with Peculiar Immunofluorescence Pattern: Report of a Rare Case. (9th November 2022) - Al-kharouf, I; Fields, T; Hamza, A
Abstract: Introduction/Objective: Hematolymphoid neoplasms are commonly associated with medical renal disease; however, association of renal cell carcinoma and nephrotic/nephritic syndrome is exceedingly rare. Paraneoplastic nephropathy in setting of renal cell carcinoma can manifest as membranous nephropathy, IgA nephropathy, or minimal change disease. The purpose of this report is to describe a rare case of clear cell renal cell carcinoma with associated membranous nephropathy with concurrent glomerular IgG and IgA deposition. Methods/Case Report: A 68-year-old male presented with a penile mass. Diagnostic work up reveled an 11cm renal mass. Urinalysis demonstrated nephrotic range proteinuria (>5 g/d). Subsequently, the patient underwent nephrectomy and penectomy. Pathologic evaluation showed clear cell renal carcinoma with sarcomatoid component and metastasis to penis. Nonneoplastic kidney workup revealed membranous glomerulopathy, with 3+ granular IgG predominantly within glomerular capillaries and 2+ IgA and 1+ C3 in a similar pattern. Electron microscopy demonstrated numerous subepithelial and intramembranous immune deposits, and few small mesangial deposits. Concurrent membranous and IgA nephropathy has been reported, but the IgA in that case is typically mesangial. The peculiar pattern of IgG and IgA deposition in this case can be seen with membranous nephropathy secondary to lupus or neoplasia. Lupus was excluded based on patient's history, serology, and absence of significant C1q staining. Therefore, the findings were consistent with membranous glomerulopathy secondary to patient's cancer. Patient's proteinuria improved after nephrectomy. He is alive and disease-free 10months after nephrectomy, with proteinuria in 0.1-0.6 g/d range. Results (if a Case Study enter NA): NA Conclusion: This case highlights the importance of thorough evaluation of non-neoplastic kidney in nephrectomy specimens for cancer, thus guiding the type of surgical intervention. Non-orthodox presentation of immunoglobulin deposition may be the herald of neoplasia in select cases.